EDUCATION OF THE GIRL-CHILD IN NIGERIA FOR A JUST, PEACEFUL, HARMONIOUS SOCIETY AND SUSTAINABLE DEVELOPMENT - Benedicta Agusiobo (Informascope, 2018)
International instruments, declarations and local laws set the pace for appropriate human development, peace and harmony.10.5 million children in Nigeria are out of school; approximately 60 percent are girls (UNICEF, 2014). They are dropouts due to various factors: socio-cultural, economic, governance etc. vulnerable to forms of abuses, harms- female genital mutilation, insurgency effects and other negative influences which deny her rights and dignity are discussed. Assessments of education statistics at basic education level over (1990-2010) revealed imbalances in enrolments and gender disparity in favour of males and the education statistics from 2014 to 2016, revealed increases in enrolments and a gender parity index ranging from 0.80 to 1.0. Various government efforts and interventions by international development partners to bridge the gender gap and heal the harms are enumerated. Benefits of educating the girl child which are critical for the development of a just, peaceful, harmonious society for sustainable development are highlighted. Recommendations included: ensuring the rights of the girl child, (development, participation protection and survival), sustaining gender equity, government`s strong political will, more funding for education, international aid, empowering  girls/women with various life  skills, ensuring girls retention and completion in school, effective implementation of the National policy on gender in basic education  etc.